ANALISIS FUNGSI ANGGARAN SEBAGAI ALAT PENGENDALIAN DAN EVALUASI KINERJA PADA PT. KUNIMOTO REZKYTAMA ABADI DI MAKASSAR - Mariati M Mariati M (Jurnal Bisnis dan Kewirausahaan, 2015)
This study aims to determine the function of the budget in control and evaluation of the work of the company at PT . Kunimoto Rezkytama Eternal in Makassar with the method used is the analysis of variance ( difference ) budget . Analysis of variance was used to compare budgeted costs to actual costs the same . Analysis of variance may indicate that the difference between the actual results with the budget that has been set before, so it can be in ketahuipenyebabdari deviations Results Discussion The results of analysis of variance is known that in 2012 the total cost of construction of houses have favorabledengan percentage deviation of 0.86 % with a difference of Rp . 80,110,909 in total project costs variable with percentage deviations 0:48 favorabel % and the amount of the difference in USD . 1.967425 billion as well as the fixed costs , the cost of these irregularities favorable to the value percentage 0:19 % and the amount of the difference in USD . 60.55 million . In 2013 , unfavorable deviation occurs at a total cost of construction of the house with a percentage of 0.36 % with the difference that berbedah Rp.6.239.332 on the total cost of the project variables , deviations in the cost of this is favorable with a percentage of 47 % with a difference of Rp . 1.939625 billion . Similarly, the project variable costs , fixed costs have favorable aberrations that occur in the total fixed cost is the percentage of the number selsisih 0:18 % Rp . 55.8 million .